Modeling Postconvective Submesoscale Coherent Vortices in the Northwestern Mediterranean Sea. Issue 12 (15th December 2017) - Damien, P.; Bosse, A.; Testor, P.; Marsaleix, P.; Estournel, C.
Abstract: For the first time, the formation of submesoscale coherent vortices (SCVs) during intermediate and deep convection events is documented in a realistic high‐resolution (1 km) numerical simulation of the oceanic circulation in the northwestern Mediterranean Sea. Winter intermediate and deep convection leads to the formation of anticyclonic and cyclonic eddies with lifetimes exceeding 1 year. By focusing on three typical eddies, the main characteristics of such vortices are discussed. The anticyclonic eddies are typical of SCVs observed in deep convection areas so far. They are characterized by a small radius (∼6.5 km) and orbital peak velocities of about 7 cm/s located at great depth (∼1500 m) or intermediate depth (∼500 m). The cyclonic vortices show very similar characteristics, such as a high Rossby number (∼0.4), but with surface‐intensified structures. The long lifetimes of both anticyclonic and cyclonic eddies reflect very slow diffusive processes between their core and their surroundings and a strong resistance to external perturbations. These long‐lived eddies are found to participate in the spreading of a significant portion (from 15 to 35%) of the convected waters in the Gulf of Lions and contribute to the ventilation of the deep basin. Key Points: Simulation of submesoscale coherent vortices formation during a convection event Detection and tracking of the submesoscale eddies Quantitative aspects related to the role of postconvective eddies